Pengembangan Media Pembelajaran Interaktif IPS Berbasis Problem Based Learning dan Ular Tangga - Dita Priska Pravita Sari; Murtono Murtono; Slamet Utomo (IKIP PGRI Bojonegoro, 2021)
This study aims to (1) developing interactive learning media based on Problem Based Learning and snakes and ladders for fourth grade social studies, (2) describe the feasibility of interactive learning media based on Problem Based Learning and snakes and ladders for fourth grade social studies This study uses Borg and Gall development, namely (1) information gathering, (2) initial product development, (3) expert evaluation, (4) product testing, (5) product revision, (6) product testing, (7) final product. This interactive learning media products are packaged on CD or soft files with a guidebook. This interactive learning media can be played on computers, laptops, and Android smartphone. Interactive learning media based on problem-based learning and snakes and ladders proved to be very feasible by seeing the results of the material expert's validation, media expert validation, linguist validation, and field practitioner validation respectively 97.50%, 96.67%, 92.50%, and 77.86% with an average percentage of eligibility reaching 91.13%. Product feasibility is also seen based on the results of field trials which show teacher responses and student responses respectively 89.28% and 81.06% with an average percentage of 85.17%. This interactive learning media is suitable for use in the fourth grade social studies.Keywords: Problem Based Learning, Snake and Ladder Games AbstrakPenelitian ini bertujuan untuk (1) mengembangkan media pembelajaran interaktif berbasis Problem Based Learning dan ular tangga pelajaran IPS Kelas IV SD, dan (2) mendeskripsikan kelayakan media pembelajaran interaktif berbasis Problem Based Learning dan ular tangga pelajaran IPS Kelas IV SD. Penelitian ini menggunakan desain pengembangan menurut Borg and Gall yakni (1) pengumpulan informasi, (2) pengembangan produk awal, (3) evaluasi ahli, (4) uji coba produk, (5) revisi produk, (6) uji coba produk, (7) produk akhir. Penelitian dan pengembangan ini menghasilkan produk media pembelajaran interaktif yang dikemas dalam bentuk CD atau soft file dilengkapi dengan buku panduan penggunaan. Media pembelajaran interaktif ini bisa dimainkan di komputer, laptop, dan smartphone Android. Media pembelajaran interaktif berbasis Problem Based Learning dan permainan ular tanggaterbukti sangat layak digunakan dengan melihat hasil validasi ahli materi, validasi ahli media, validasi ahli bahasa, dan validati praktisi lapangan berturut-turut 97,50 %, 96,67 %, 92,50 %, dan 77,86% dengan rata-rata persentase kelayakan mencapai 91,13%. Kelayakan produk juga dilihat berdasarkan hasil ujicoba lapangan yang menunjukkan respon guru dan respon siswa berturut-turut 89,28 % dan 81,06 % dengan rata-rata persentase sebesar 85,17 %. Media pembelajaran interaktif ini layak digunakan pada mata pelajaran IPS kelas IV SD.Kata kunci: Problem Based Learning, Permainan Ular Tangga